Tinjauan Hukum Perjanjian Penitipan Barang yang Dilakukan melalui Anak Buah Kapal: Studi Kasus di Pelabuhan Punggur Kota Batam - Nuriani, Lia; Suryadi, Suryadi; Budiyanti, Eka Rus (Penerbit Goodwood, 2023)
Purpose: This research was conducted to find out about the phenomenon of safekeeping of goods with Ship's Crew (ABK) in Punggur Harbor, Batam City. Methodology : This study uses a type or method of normative legal research, in which the research is carried out by examining legal materials related to cases of safekeeping of goods against Ship's Crews (ABK). Then after that it was continued by examining additional data in the form of interviews conducted with Ship's Crew (ABK) at Punggur Port, Batam City, which later became Normative-Empirical legal research. Result: The result is reveals that agrarian policies in Bintan have led to the loss of land ownership rights for many coastal communities due to lack of consultation, inadequate compensation, and insufficient protection of traditional land tenure systems. Limitation: The ship's crew is the other crew than the captain. The phenomenon of entrusting goods to ship crew is very common for people who are used to life in the port. So it is not uncommon for many Ship's Crew to be reluctant to reject things that are considered normal by the people around them. Contribution: The analysis aims to contribute to the ongoing debate on land rights and coastal development in Indonesia by providing a legal perspective on the issue. It also highlights the need for greater recognition of the rights of coastal communities in agrarian policies and regulatory frameworks.